1991
DOI: 10.1111/j.1365-2141.1991.tb07976.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia B Leyden arising de novo by point mutation in the putative factor IX promoter region

Abstract: Haemophilia B Leyden is characterized by severe factor IX deficiency during childhood with partial resolution at puberty or following the administration of anabolic steroids. The disorder has recently been associated with point mutations in the putative factor IX promoter region, which contains an imperfect direct repeat spanning a possible start site of transcription. We have identified a T to C transition at position +8 in the promoter region of a patient with the haemophilia B Leyden phenotype. A mutation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…It has been found that promoter mutations in factor IX (4,7,12,19,28,39,45,47,49), protein C (2), haptoglobin (16), and ␤-globin (10,31,(36)(37)(38) lead to disruption of the binding of transcription factors, with a resulting clinically significant reduction of gene expression. Such a lesion might be expected to affect the level of expression of the factor VIII protein and give rise to a clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that promoter mutations in factor IX (4,7,12,19,28,39,45,47,49), protein C (2), haptoglobin (16), and ␤-globin (10,31,(36)(37)(38) lead to disruption of the binding of transcription factors, with a resulting clinically significant reduction of gene expression. Such a lesion might be expected to affect the level of expression of the factor VIII protein and give rise to a clinical phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…These studies estimate the "r" within the past 150 years, assuming the half-life of a severe X-linked mutation is two generations (Haldane 1935). However, because of small 635 6 Transversions 2 18 c,f 9 Deletions/insertions (<20 bp) e 4 1 b,c 0.25 Deletions (>20 bp) 2 3 1.50 Insertions 0 2 -All mutations 14 47 a Includes germline and somatic origins described herein and in the following references: (Vidaud et al 1986Tanimoto et al 1988;Bottema et al 1989Bottema et al , 1990Koeberl et al 1990;Montandon et al 1990;Royle et al 1991;Taylor et al 1991;Kling et al 1992;Ludwig et al 1992;Thompson et al 1992;Ketterling et al 1993;Knobloch et al 1993;Giannelli et al 1996; Thompson and Chen 1994;Vielhaber et al 1994) b Does not include the following four erroneously reported germline origins in Knobloch et al (1993): Malmö 20 (R-4 W origin ≠MF); Malmö 8 (∆6,398-9, origin ≠MF); Malmö 10 (∆6,666-75, origin ≠MF); Malmö 44 (∆20,398, origin ≠MF); P. Green, personal communication c Includes one somatic mosaic d Includes two somatic mosaics e Includes one family with a combined deletion/insertion f Includes two paternal origins defined in sporadic families with female hemophiliacs g Does not include factor IX Marseille (T-20 C, origin ≠MF) since the germline origin could not be established in the maternal grandfather who was deceased and this mutation is associated with mild disease (Ghanem et al 1993) sample sizes, "r" estimates for specific mutation types have not been attempted in either humans or rodents. Their data consist of point mutation analyses and suggest an overall "male-driven evolution" (an estimated "r" of 6).…”
Section: Potential Biasesmentioning
confidence: 96%
“…For factor IX, the study of gene expression has been rendered particularly interesting by the existence of the hemophilia B Leyden variants. A detailed molecular characterization of the factor IX gene from patients with the Leyden variant has revealed a number of defects, all clustered within a 33 bp region adjacent to the start site of transcription in the promoter region of the gene [15][16][17][18][19][20][21][22][23]. The Leyden phenotype was initially described in 1970 [14].…”
Section: Spontanous Remission Of Severe Hemophilia B (Fix Leyden)mentioning
confidence: 99%